Transmissive resin composition for laser cladding, composition combination, molded product, and method for producing the molded product

By using glass sheets with a thickness of 0.1 to 2 μm and polyamide resins and other materials in laser melting technology, resin compositions with mechanical strength, low warpage and high light transmittance are prepared, which solves the problems of insufficient material performance and environmental pollution in traditional technology, and is suitable for efficient manufacturing of complex components.

CN115698184BActive Publication Date: 2025-03-07RYOGLOBAL POLYOXYMETHYLENE CO LTD
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202180038411.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-05-25
Filing Date
2021-05-20
Publication Date
2025-03-07
Estimated Expiration
2041-05-20

AI Technical Summary

Technical Problem

In the existing laser melting technology, it is difficult to find materials with mechanical strength, low warpage and high light transmittance, especially when manufacturing complex components, there are problems of poor material flowability and environmental pollution.

Method used

By using a glass sheet with a thickness of 0.1 to 2 μm as a reinforcing filler, a polyamide resin and a translucent pigment were combined with a polyamide resin and a translucent pigment, a translucent resin composition for laser melting with mechanical strength, low warpage and high light transmittance was prepared.

Benefits of technology

It achieves excellent performance of mechanical strength, low warpage and light transmittance, solves the problems of poor material flowability and environmental pollution in traditional welding technology, and is suitable for the manufacturing of complex components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115698184B_ABST
    Figure CN115698184B_ABST
Patent Text Reader

Abstract

The present invention provides a transmissive resin composition for laser cladding having excellent physical properties such as mechanical strength and low warpage and high light transmittance, a composition combination, a molded product, and a method for manufacturing the molded product. The transmissive resin composition for laser cladding comprises 10 to 120 parts by mass of a glass sheet having a thickness of 0.1 to 2 μm and a translucent pigment relative to 100 parts by mass of a crystalline thermoplastic resin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a transmissive resin composition for laser cladding, a composition combination, a molded product, and a method for producing the molded product. Background Art

[0002] Thermoplastic resins are easy to process and are widely used in vehicle parts, electrical / electronic equipment parts, other precision instrument parts, etc., due to their excellent properties. Recently, parts with complex shapes can also be made of thermoplastic resins, especially crystalline thermoplastic resins. In the bonding of parts with hollow parts such as intake manifolds, various welding technologies such as adhesive welding, vibration welding, ultrasonic welding, hot plate welding, injection welding, and laser welding can be used.

[0003] However, welding with adhesives not only takes time until solidification, but also has environmental impact issues such as pollution of the surrounding area. Ultrasonic welding, hot plate welding, etc. have been pointed out to cause damage to products due to vibration and heat, wear powder, burrs, etc., and require post-processing. In addition, injection welding often requires special molds and molding machines, and there are problems such as it cannot be used when the material has poor fluidity.

[0004] On the other hand, laser cladding is a method of joining a resin member that is transmissive to laser light (also called non-absorbent or weakly absorptive) (hereinafter sometimes referred to as a "transmissive resin member") and a resin member that is absorptive to laser light (hereinafter sometimes referred to as an "absorbent resin member") by contacting and cladding the two resin members. Specifically, it is a method of joining by irradiating the joining surface with laser light from the transmissive resin member side and using the energy of the laser to melt the absorptive resin member forming the joining surface. Laser cladding does not produce wear powder or burrs, and causes little damage to the product. In addition, polyamide resin itself is a material with a high laser transmittance. Therefore, the processing of polyamide resin products based on laser cladding technology has recently attracted attention.

[0005] The above-mentioned transmissive resin component can usually be obtained by molding a translucent resin composition. As such a translucent resin composition, Patent Document 1 discloses a resin composition for laser cladding, which is a resin composition formed by mixing (B) 1 to 150 parts by mass of a reinforcing filler having a refractive index of 1.560 to 1.600 at 23°C with respect to 100 parts by mass of (A) polyamide resin, and at least one monomer constituting at least one of the above-mentioned (A) polyamide resins contains an aromatic ring. In the examples of Patent Document 1, a resin composition in which glass fiber and a colorant are mixed in a mixture of polyamide MXD6 and polyamide 66, or a mixture of polyamide 6I / 6T and polyamide 6 is disclosed.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Publication No. 2008-308526 Summary of the invention

[0009] Problems to be solved by the invention

[0010] Here, as laser cladding technology advances, new materials are required, especially materials with excellent physical properties such as mechanical strength and low warpage, and high light transmittance.

[0011] The present invention aims to solve the above-mentioned problems and to provide a transmissive resin composition for laser cladding having excellent physical properties such as mechanical strength and low warpage and high light transmittance, a composition combination, a molded product, and a method for producing the molded product.

[0012] Solutions to the problem

[0013] Based on the above problems, the inventors have conducted research and found that the above problems can be solved by using a glass sheet with a thickness of 0.1 to 2 μm as a reinforcing filler. Specifically, the above problems were solved by the following method.

[0014] <1> A translucent resin composition for laser cladding, comprising 10 to 120 parts by mass of a glass flake having a thickness of 0.1 to 2 μm and a translucent pigment, based on 100 parts by mass of a crystalline thermoplastic resin.

[0015] <2> The resin composition according to <1>, wherein

[0016] The light-transmitting pigment has a perylene skeleton.

[0017] <3> The resin composition according to <1> or <2>, wherein

[0018] The above-mentioned crystalline thermoplastic resin includes a polyamide resin.

[0019] <4> The resin composition according to <3>, wherein

[0020] The polyamide resin comprises a diamine-derived structural unit and a dicarboxylic acid-derived structural unit, wherein 70 mol% or more of the diamine-derived structural unit is derived from xylylenediamine, 70 mol% or more of the dicarboxylic acid-derived structural unit is derived from an α,ω-straight-chain aliphatic dicarboxylic acid having 4 to 20 carbon atoms, and 30 mol% or more of the xylylenediamine-derived structural unit is a meta-xylylenediamine-derived structural unit.

[0021] <5> The resin composition according to any one of <1> to <4>, wherein

[0022] When the resin composition is molded into a molded article having a thickness of 60 mm×60 mm×1 mm, the warpage of the molded article is less than 1 mm.

[0023] The warpage amount refers to the difference between the height of the highest part of the molded product placed on a reference stand and the height of the lowest part of the test piece.

[0024] <6> The resin composition according to any one of <1> to <5>, wherein

[0025] The crystalline thermoplastic resin includes a polyamide resin having a crystallization heat of 0 to -1 mJ / mg when measured by a differential scanning calorimeter.

[0026] <7> A composition comprising:

[0027] The resin composition according to any one of <1> to <6>, and

[0028] A light-absorbing resin composition comprising a thermoplastic resin and a light-absorbing pigment.

[0029] <8> A molded article formed from the resin composition according to any one of <1> to <6> or a combination of the composition according to <7>.

[0030] <9> A method for manufacturing a molded article, the method comprising:

[0031] Laser welding is performed on a molded article formed of the resin composition according to any one of <1> to <6> and a molded article formed of a light-absorbing resin composition containing a thermoplastic resin and a light-absorbing dye.

[0032] Effects of the Invention

[0033] The present invention can provide a transmissive resin composition for laser cladding having excellent physical properties such as mechanical strength and low warpage and high light transmittance, a composition combination, a molded product, and a method for producing the molded product. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is a schematic diagram for explaining a method for measuring the warpage height in the example.

[0035] Explanation of symbols

[0036] 1 Benchtop

[0037] 2 Test pieces for light-transmitting components

[0038] 3 The highest part of the height

[0039] 4 Warping DETAILED DESCRIPTION

[0040] Hereinafter, a mode for implementing the present invention (hereinafter, simply referred to as "this embodiment") will be described in detail. It should be noted that the following this embodiment is an example for describing the present invention, and the present invention is not limited to this embodiment.

[0041] In addition, in this specification, "to" is used in the meaning which includes the numerical value described before and after it as a lower limit and an upper limit.

[0042] In this specification, various physical property values ​​and characteristic values ​​are values ​​at 23° C. unless otherwise specified.

[0043] The transmissive resin composition for laser cladding of the present embodiment (hereinafter, sometimes referred to as "the resin composition of the present embodiment") comprises a crystalline thermoplastic resin, a glass sheet and a translucent pigment, wherein 10 to 120 parts by mass of a glass sheet having a thickness of 0.1 to 2 μm are contained relative to 100 parts by mass of the crystalline thermoplastic resin. By setting such a structure, a transmissive resin composition for laser cladding having excellent physical properties such as mechanical strength and low warpage and high transmittance can be provided. Inorganic fillers have always been used to achieve mechanical strength, low warpage, etc. However, it has been completely unknown that the shape of the inorganic filler will affect the transmittance. In the present invention, it was unexpectedly found that by using a glass sheet having a thickness of 0.1 to 2 μm as an inorganic filler, in addition to mechanical strength and low warpage, the transmittance can also be improved.

[0044] <Crystalline thermoplastic resin>

[0045] The resin composition of the present embodiment comprises crystalline thermoplastic resin.As crystalline thermoplastic resin, polyamide resin, polyacetal resin, polyester resin (preferably polybutylene terephthalate resin) etc. can be exemplified, preferably polyamide resin and polybutylene terephthalate resin, more preferably polyamide resin.If crystalline polyamide resin is used, then when molded product is molded, it can be solidified faster.In addition, if crystalline polyamide resin is used, then the resin composition obtained has the tendency that oil resistance, grease resistance, lubricity, sliding property, wear resistance, friction resistance are also excellent.

[0046] The crystalline thermoplastic resin refers to a thermoplastic resin having a "crystalline portion" in which molecules are regularly arranged when the temperature of the resin is lowered to the crystallization temperature and the resin solidifies.

[0047] Preferably, the crystalline thermoplastic resin accounts for 30% by mass or more of the resin composition of the present embodiment, more preferably 40% by mass or more, and further preferably 45% by mass or more. In addition, the upper limit of the content of the crystalline thermoplastic resin in the resin composition is preferably 90% by mass or less, more preferably 80% by mass or less, and further preferably 75% by mass or less.

[0048] The resin composition of the present embodiment may contain only one type of crystalline thermoplastic resin, or may contain two or more types of crystalline thermoplastic resins. When containing two or more types of crystalline thermoplastic resins, the total amount is preferably within the above range.

[0049] <<Polyamide resin>>

[0050] The polyamide resin used in the present embodiment is not particularly limited, and a known polyamide resin can be used. For example, as the polyamide resin, the description in paragraphs 0011 to 0013 of JP-A-2011-132550 can be referred to.

[0051] The polyamide resin used in the present embodiment may be an aliphatic polyamide resin or a semi-aromatic polyamide resin, and is preferably a semi-aromatic polyamide resin.

[0052] Examples of the aliphatic polyamide resin include polyamide 6, polyamide 11, polyamide 12, polyamide 46, polyamide 66, polyamide 610, polyamide 612, polyamide 1010, and polyamide 1012.

[0053] On the other hand, as a semi-aromatic polyamide resin, there can be exemplified a semi-aromatic polyamide resin composed of a structural unit derived from a diamine and a structural unit derived from a dicarboxylic acid, and 30 to 70 mol% of the total structural units of the structural units derived from the diamine and the structural units derived from the dicarboxylic acid are structural units containing aromatic rings, and more preferably 40 to 60 mol% of the total structural units of the structural units derived from the diamine and the structural units derived from the dicarboxylic acid are structural units containing aromatic rings. By using such a semi-aromatic polyamide resin, the mechanical strength of the obtained molded product can be improved. As a semi-aromatic polyamide resin, there can be exemplified a terephthalic acid polyamide resin (polyamide 6T, polyamide 9T), a xylylenediamine polyamide resin described later, and the like.

[0054] At least one of the polyamide resins used in the present embodiment contains structural units derived from diamines and structural units derived from dicarboxylic acids, preferably 70 mol% or more of the structural units derived from diamines are derived from xylylenediamine (preferably 30 mol% or more of the structural units derived from xylylenediamine are structural units derived from meta-xylylenediamine), and 70 mol% or more of the structural units derived from dicarboxylic acids are preferably polyamide resins derived from α,ω-straight-chain aliphatic dicarboxylic acids having 4 to 20 carbon atoms (hereinafter sometimes referred to as "xylylenediamine-based polyamide resins").

[0055] More preferably, 75 mol% or more, further preferably 80 mol% or more, further preferably 90 mol% or more, further preferably 95 mol% or more of the structural units derived from diamine in the xylylenediamine-based polyamide resin are derived from xylylenediamine. More preferably, 75 mol% or more, further preferably 80 mol% or more, further preferably 90 mol% or more, further preferably 95 mol% or more of the structural units derived from dicarboxylic acid in the xylylenediamine-based polyamide resin are derived from α,ω-straight-chain aliphatic dicarboxylic acid having 4 to 20 carbon atoms.

[0056] The xylylenediamine is preferably p-xylylenediamine and / or m-xylylenediamine, more preferably at least m-xylylenediamine, and further preferably 30 mol% or more (preferably 40 mol% or more, more preferably 50 mol% or more, and further preferably 60 mol% or more) of the xylylenediamine is m-xylylenediamine. More preferably, 30 to 90 mol% (preferably 60 to 90 mol%) of the xylylenediamine is m-xylylenediamine, and 70 to 10 mol% (preferably 40 to 10 mol%) is p-xylylenediamine. The total amount of m-xylylenediamine and p-xylylenediamine is 100 mol% or less of the raw material diamine, preferably 90 to 100 mol%.

[0057] Examples of diamines other than m-xylylenediamine and p-xylylenediamine that can be used as the raw material diamine component of the xylylenediamine-based polyamide resin include aliphatic diamines such as tetramethylenediamine, pentamethylenediamine, 2-methylpentamethylenediamine, hexamethylenediamine, heptamethylenediamine, octamethylenediamine, nonamethylenediamine, decamethylenediamine, dodecamethylenediamine, 2,2,4-trimethylhexamethylenediamine, and 2,4,4-trimethylhexamethylenediamine; and 1, Alicyclic diamines such as 3-bis(aminomethyl)cyclohexane, 1,4-bis(aminomethyl)cyclohexane, 1,3-diaminocyclohexane, 1,4-diaminocyclohexane, bis(4-aminocyclohexyl)methane, 2,2-bis(4-aminocyclohexyl)propane, bis(aminomethyl)decalin, and bis(aminomethyl)tricyclodecane; and diamines having an aromatic ring such as bis(4-aminophenyl)ether, p-phenylenediamine, and bis(aminomethyl)naphthalene can be used alone or in combination of two or more.

[0058] Preferred α,ω-straight-chain aliphatic dicarboxylic acids having 4 to 20 carbon atoms as the raw material dicarboxylic acid component of the xylylenediamine-based polyamide resin include, for example, succinic acid, glutaric acid, pimelic acid, suberic acid, azelaic acid, adipic acid, sebacic acid, undecanedioic acid, dodecanedioic acid and the like. One or more of them can be used in combination. Among them, adipic acid or sebacic acid is more preferred because the melting point of the polyamide resin is in a range suitable for molding processing.

[0059] Examples of dicarboxylic acid components other than the above-mentioned α,ω-straight-chain aliphatic dicarboxylic acids having 4 to 20 carbon atoms include phthalic acid compounds such as isophthalic acid, terephthalic acid, and phthalic acid, and isomers of naphthalene dicarboxylic acids such as 1,2-naphthalene dicarboxylic acid, 1,3-naphthalene dicarboxylic acid, 1,4-naphthalene dicarboxylic acid, 1,5-naphthalene dicarboxylic acid, 1,6-naphthalene dicarboxylic acid, 1,7-naphthalene dicarboxylic acid, 1,8-naphthalene dicarboxylic acid, 2,3-naphthalene dicarboxylic acid, 2,6-naphthalene dicarboxylic acid, and 2,7-naphthalene dicarboxylic acid. These can be used alone or in combination of two or more.

[0060] It should be noted that, although the main components are composed of structural units derived from diamines and structural units derived from dicarboxylic acids, structural units other than these are not completely excluded, and structural units derived from lactams such as ε-caprolactam and laurolactam, and structural units derived from aliphatic aminocarboxylic acids such as aminocaproic acid and aminoundecanoic acid may also be included. Here, the main component means that among the structural units constituting the xylylenediamine polyamide resin, the total number of structural units derived from diamines and structural units derived from dicarboxylic acids is the largest among all structural units. In this embodiment, it is preferred that the total number of structural units derived from diamines and structural units derived from dicarboxylic acids in the xylylenediamine polyamide resin accounts for more than 90% of all structural units, and more preferably accounts for more than 95%.

[0061] The crystalline thermoplastic resin used in this embodiment preferably includes a polyamide resin having a crystallization heat of 0 to -1 mJ / mg when measured by a differential scanning calorimeter, and more preferably includes a polyamide resin having a crystallization heat of 0 to -0.8 mJ / mg. By using such a polyamide resin, crystallization is effectively carried out, and there is a tendency that the mechanical strength is not easily significantly reduced even when water is absorbed over time. The crystallization heat mentioned here refers to the value measured under the conditions described in the examples described later.

[0062] As an embodiment of the resin composition of the present embodiment, a mode that substantially does not include thermoplastic resins other than polyamide resins can be cited. Substantially not including means that the content of thermoplastic resins other than polyamide resins is preferably less than 5% by mass of the resin composition of the present embodiment, more preferably less than 3% by mass, and further preferably less than 1% by mass.

[0063] In addition, as the polyacetal resin used in this embodiment, the records of paragraphs 0009 to 0012 of Japanese Patent Publication No. 2019-123836 can be referred to, and the content is introduced into this specification. As the polybutylene terephthalate resin used in this embodiment, the records of paragraphs 0016 to 0024 of Japanese Patent Publication No. 2020-019950 can be referred to, and the content is introduced into this specification.

[0064] <Glass piece>

[0065] The resin composition of the present embodiment contains 10 to 120 parts by mass of a glass flake having a thickness of 0.1 to 2 μm with respect to 100 parts by mass of a crystalline thermoplastic resin. With such a configuration, in addition to mechanical strength and low warpage, light transmittance can be improved.

[0066] In the present embodiment, the thickness of the glass sheet refers to the average thickness. The thickness of the glass sheet is preferably 0.3 μm or more, more preferably 0.4 μm or more, further preferably 0.5 μm or more, and further preferably 0.6 μm or more. In addition, the thickness of the glass sheet is preferably 1.8 μm or less, more preferably 1.6 μm or less, further preferably 1.4 μm or less, further preferably 1.2 μm or less, further preferably 1.0 μm or less, and further preferably 0.8 μm or less. Here, the average thickness is measured by the following method.

[0067] <<Method for measuring average thickness>>

[0068] The thickness of more than 100 glass sheets was measured using a scanning electron microscope (SEM), and the measured values ​​were averaged to obtain the thickness. The sample stage of the SEM was adjusted using a sample stage micro-movement device so that the cross section (thickness plane) of the glass sheet was perpendicular to the irradiation electron beam axis of the SEM.

[0069] In the present embodiment, the numerical average value of the aspect ratio of the glass piece is preferably 3 to 20. The aspect ratio can also be measured by the same method as the above-mentioned method for measuring the average thickness.

[0070] The glass composition of the glass sheet may be any of various glass compositions represented by A glass, C glass, D glass, R glass, S glass, and E glass, and is not particularly limited.

[0071] The resin composition of the present embodiment contains 10 to 120 parts by mass of a glass sheet having a thickness of 0.1 to 2 μm relative to 100 parts by mass of a crystalline thermoplastic resin. The glass sheet is preferably 20 parts by mass or more, more preferably 30 parts by mass or more, further preferably 35 parts by mass or more, further preferably 40 parts by mass or more, and may also be 45 parts by mass or more, 60 parts by mass or more, 80 parts by mass or more, or 90 parts by mass or more. In addition, the glass sheet having a thickness of 0.1 to 2 μm is preferably 120 parts by mass or less, more preferably 115 parts by mass or less, further preferably 110 parts by mass or less, and may also be 105 parts by mass or less relative to 100 parts by mass of a crystalline thermoplastic resin.

[0072] The glass flakes having a thickness of 0.1 to 2 μm preferably occupy 10 to 60% by mass, more preferably 20 to 60% by mass, and may also occupy 25 to 55% by mass in the resin composition of the present embodiment.

[0073] The resin composition of the present embodiment may contain only one type of glass flakes having a thickness of 0.1 to 2 μm, or may contain two or more types. When containing two or more types, the total amount is preferably within the above range.

[0074] The resin composition of the present embodiment may contain other inorganic fillers in addition to the glass flake having a thickness of 0.1 to 2 μm, or may not contain other inorganic fillers.

[0075] Examples of other inorganic fillers include fibrous, flaky, spherical, and needle-shaped inorganic fillers, and examples of components thereof include glass, metal oxides, metal hydroxides, carbonates, and sulfates.

[0076] An example of an embodiment of the resin composition of the present embodiment is a resin composition that substantially does not contain other inorganic fillers except a glass sheet with a thickness of 0.1 to 2 μm. Substantially containing means that the content of inorganic fillers other than the glass sheet with a thickness of 0.1 to 2 μm is less than 5% by mass of the total amount of inorganic fillers contained in the resin composition, preferably less than 3% by mass, and more preferably less than 1% by mass.

[0077] It should be noted that the inorganic filler in the present embodiment does not include an inorganic filler that is a nucleating agent.

[0078] <Light-transmitting pigment>

[0079] The resin composition of the present embodiment includes a translucent pigment. By including a translucent pigment, the obtained molded product can have a color tone, and the appearance of the molded product can be improved. In particular, the color tone of the transmissive resin component molded by the resin composition of the present embodiment and the absorption resin component described in detail later can be unified, and the appearance of the obtained molded product (laser welded product) can be improved.

[0080] The light-transmitting pigment used in the present embodiment is usually a black pigment, and specifically includes pigments having a skeleton selected from a nigrosine skeleton, a naphthalocyanine skeleton, an aniline black skeleton, a phthalocyanine skeleton, a porphyrin skeleton, a perinone skeleton, a quaterrylene skeleton, an azo skeleton, an anthraquinone skeleton, a pyrazolone skeleton, a squaric acid derivative skeleton, a perylene skeleton, a chromium complex, and an immonium skeleton, preferably a pigment having a perylene skeleton.

[0081] The light-transmitting dye refers to, for example, a dye in which a total of 100 mass % of a polyamide resin, 30 mass % of a glass sheet, and 0.2 mass % of a dye (a dye considered to be a light-transmitting dye) are mixed, and when the light transmittance at a wavelength of 1060 nm is measured by the measuring method described in the examples described later, the transmittance becomes 2% or more.

[0082] The light-transmitting dye may be a dye or a pigment, and is preferably a pigment.

[0083] Examples of commercially available products include colorants (pigments) e-BIND LTW-8731H and e-BIND LTW-8701H manufactured by Orient Chemical Industries, colorants Plast Yellow 8000, Plast Red M 8315, and Oil Green 5602 manufactured by Arimoto Chemical Co., Ltd., colorants Macrolex Yellow 3G, Macrolex Red EG, and Macrolex Green 3 manufactured by LANXESS, and colorants Spectrasence K0087 (formerly known as Lumogen (registered trademark) Black K0087 and Lumogen Black FK4280) and Spectrasence K0088 (formerly known as Lumogen Black K0088 and Lumogen Black FK4281) manufactured by BASF.

[0084] In 100 parts by mass of resin combination, the content of the light-transmitting pigment in the resin combination of the present embodiment is preferably more than 0.001 parts by mass, more preferably more than 0.01 parts by mass, and then can also be more than 0.08 parts by mass, more than 0.1 parts by mass, more than 0.15 parts by mass, more than 0.2 parts by mass. In addition, in 100 parts by mass of resin combination, the upper limit of the content of the light-transmitting pigment is preferably less than 5.0 parts by mass, more preferably less than 3.0 parts by mass, further preferably less than 1.0 parts by mass, and can also be less than 0.8 parts by mass, less than 0.5 parts by mass, less than 0.4 parts by mass, less than 0.3 parts by mass.

[0085] The resin composition may contain only one type of light-transmitting dye, or may contain two or more types. When containing two or more types, the total amount is preferably within the above range.

[0086] In addition, the transmissive resin composition for laser cladding of the present embodiment preferably contains substantially no carbon black. Substantially containing no carbon black means, for example, that the carbon black content is 0.0001% by mass or less of the resin composition.

[0087] <Nucleating agent>

[0088] The resin composition of the present embodiment may contain a nucleating agent.

[0089] The nucleating agent is not particularly limited as long as it is a substance that does not melt during melt processing and can form crystal nuclei during cooling. Among them, talc and calcium carbonate are preferred, and talc is more preferred.

[0090] The lower limit of the number average particle size of the nucleating agent is preferably 0.1 μm or more, more preferably 1 μm or more, and further preferably 3 μm or more. The upper limit of the number average particle size of the nucleating agent is preferably 40 μm or less, more preferably 30 μm or less, further preferably 28 μm or less, further preferably 15 μm or less, and further more preferably 10 μm or less.

[0091] The ratio of the nucleating agent in the resin composition of the present embodiment is preferably 0.01 to 1% by mass, more preferably 0.1% by mass or more, and more preferably 0.5% by mass or less.

[0092] The resin composition of the present embodiment may contain only one type of nucleating agent, or may contain two or more types. When containing two or more types, the total amount is preferably within the above range.

[0093] <Copper compounds>

[0094] The resin composition of the present embodiment may contain a copper compound. By using a copper compound, significantly excellent heat aging resistance can be achieved.

[0095] Examples of the copper compound used in this embodiment include copper halides (e.g., copper iodide, copper bromide, and copper chloride) and copper acetate, preferably selected from cuprous iodide, cupric iodide, cuprous bromide, cupric bromide, cuprous acetate, cupric acetate, cuprous chloride, and cupric chloride, and more preferably selected from cuprous iodide, cuprous acetate, and cuprous chloride.

[0096] In addition, the copper compound is preferably used in combination with an alkali metal halide described below. When the copper compound and the alkali metal halide are used in combination, the mixture is preferably a 1:1 to 1:15 (mass ratio) copper compound:alkali metal halide, more preferably a 1:1 to 1:5 mixture, and even more preferably a 1:2 to 1:4 mixture.

[0097] Regarding the case of combining a copper compound with an alkali metal halide, reference may also be made to the description in paragraphs 0046 to 0048 of JP-A-2013-513681, and these contents are incorporated into the present specification.

[0098] The ratio of the copper compound in the resin composition of the present embodiment is preferably 0.01 to 1% by mass, more preferably 0.03% by mass or more, further preferably 0.05% by mass or more, and more preferably 0.5% by mass or less.

[0099] The resin composition of the present embodiment may contain only one copper compound or two or more copper compounds. When containing two or more copper compounds, the total amount is preferably within the above range.

[0100] <Alkali metal halides>

[0101] The alkali metal halide used in the present embodiment refers to a halide of an alkali metal. As the alkali metal, potassium and sodium are preferred, and potassium is more preferred. In addition, as the halogen atom, iodine, bromine, and chlorine are preferred, and iodine is more preferred. As specific examples of the alkali metal halide used in the present embodiment, potassium iodide, potassium bromide, potassium chloride, and sodium chloride can be exemplified, and potassium iodide is preferred.

[0102] The ratio of the alkali metal halide in the resin composition of the present embodiment is preferably 0.01 to 1% by mass, more preferably 0.1% by mass or more, and more preferably 0.5% by mass or less.

[0103] The resin composition of the present embodiment may contain only one type of alkali metal halide, or may contain two or more types. When containing two or more types, the total amount is preferably within the above range.

[0104] <Mold release agent>

[0105] The resin composition of the present embodiment preferably contains a mold release agent. By containing a mold release agent, when molding is performed using a mold such as injection molding, the releasability from the mold can be improved.

[0106] The release agent preferably contains at least one selected from amide wax and fatty acid metal salt, and more preferably contains fatty acid metal salt.

[0107] Examples of the amide wax include carboxamide wax and bisamide wax, and carboxamide wax is preferred.

[0108] Carboxamide waxes are obtained, for example, by dehydration reaction of a mixture of a higher aliphatic monocarboxylic acid and a polybasic acid with a diamine compound. As the higher aliphatic monocarboxylic acid, preferably a saturated aliphatic monocarboxylic acid and a hydroxycarboxylic acid having 16 or more carbon atoms, for example, palmitic acid, stearic acid, behenic acid, montanic acid, 12-hydroxystearic acid, etc. As the polyacid, carboxylic acids higher than dibasic acids, for example, aliphatic dicarboxylic acids such as malonic acid, succinic acid, adipic acid, sebacic acid, pimelic acid, and azelaic acid, aromatic dicarboxylic acids such as phthalic acid and terephthalic acid, and alicyclic dicarboxylic acids such as cyclohexanedicarboxylic acid and cyclohexylsuccinic acid, etc. can be mentioned.

[0109] As a diamine compound, hexamethylenediamine, 1, 3- diaminopropane, 1, 4- diaminobutane, hexamethylenediamine, meta-xylylenediamine, toluenediamine, p-xylylenediamine, phenylenediamine, isophoronediamine etc. are mentioned, for example.

[0110] For the carboxamide wax in this embodiment, the softening point can be arbitrarily adjusted by changing the mixing ratio of the polyacid relative to the higher aliphatic monocarboxylic acid used in the manufacture of the carboxamide wax. The mixing ratio of the polyacid is preferably in the range of 0.18 to 1 mole relative to 2 moles of the higher aliphatic monocarboxylic acid. In addition, the amount of the diamine compound is preferably in the range of 1.5 to 2 moles relative to 2 moles of the higher aliphatic monocarboxylic acid, which varies depending on the amount of the polyacid used.

[0111] Examples of the bisamide wax include compounds of diamine compounds such as N,N′-methylenebisstearamide and N,N′-ethylenebisstearamide and fatty acids, and dioctadecyl diamides such as N,N′-dioctadecyl terephthalamide.

[0112] The fatty acid metal salt is preferably a metal salt of a long-chain fatty acid having 16 to 36 carbon atoms, examples of which include metal stearates such as calcium stearate, zinc stearate, aluminum stearate, sodium stearate, and lithium stearate, and metal montanates such as calcium montanate and sodium montanate, preferably metal montanates.

[0113] Examples of the release agent include esters of aliphatic carboxylic acids and alcohols, aliphatic hydrocarbon compounds having a number average molecular weight of 200 to 15,000, polysiloxane silicone oils, ketone waxes, and the like, in addition to the above-mentioned release agents.

[0114] For details of the release agent, reference can be made to the description in paragraphs 0055 to 0061 of Japanese Patent Application Publication No. 2018-095706 and the description in paragraphs 0022 to 0027 of Japanese Patent Application Publication No. 2019-108526, and these contents are incorporated into this specification.

[0115] In resin composition, the content of the releasing agent in the resin composition of the present embodiment is preferably more than 0.05 mass %, more preferably more than 0.1 mass %, and further preferably more than 0.2 mass %. By being set to more than the above-mentioned lower limit, there is a tendency that demoulding property further improves. In addition, the content of the above-mentioned releasing agent is preferably less than 3 mass %, more preferably less than 2 mass %, further preferably less than 1 mass %, further preferably less than 0.8 mass %, and further preferably less than 0.6 mass %.

[0116] The resin composition of the present embodiment may contain only one type of release agent, or may contain two or more types. When containing two or more types, the total amount is preferably within the above range.

[0117] <Other ingredients>

[0118] Without departing from the scope of the present embodiment, the resin composition of the present embodiment may include other ingredients. As such additives, fillers, light stabilizers, antioxidants, ultraviolet absorbers, fluorescent whitening agents, anti-dripping agents, antistatic agents, antifogging agents, anti-adhesion agents, flow improvers, plasticizers, dispersants, antiviral agents, antibacterial agents, flame retardants, etc., except for glass sheets with a thickness of 0.1 to 2 μm, can be cited. These ingredients can be used only one or in combination of two or more. The flame retardant is preferably a phosphorus flame retardant. As phosphorus flame retardants, phosphazene flame retardants, phosphonate flame retardants, and diphosphonate flame retardants can be exemplified.

[0119] It should be noted that, for the resin composition of the present embodiment, the content of the crystalline thermoplastic resin (preferably a polyamide resin), a glass sheet with a thickness of 0.1 to 2 μm, and a light-transmitting pigment, a nucleating agent, a copper compound, an alkali metal halide, a release agent, and other additives is adjusted in such a manner that the total of each component becomes 100% by mass. In the present embodiment, the total of the crystalline thermoplastic resin, the glass sheet with a thickness of 0.1 to 2 μm, and the selectively added nucleating agent, copper compound, alkali metal halide, and a release agent is exemplified to account for more than 99% by mass of the resin composition.

[0120] <Physical properties of resin composition>

[0121] The resin composition of the present embodiment preferably has small warpage when made into a molded product. Specifically, when the resin composition of the present embodiment is molded into a molded product with a thickness of 60mm×60mm×1mm, the warpage of the molded product is preferably less than 2mm, more preferably less than 1mm, and further preferably less than 0.9mm. The warpage refers to the difference between the height of the highest part and the height of the lowest part of the test piece when the molded product is placed on a reference table. The details are described in the embodiments described below. The lower limit of the warpage is ideally 0mm, but in practice it is greater than 0.05mm.

[0122] The resin composition of the present embodiment is molded into an ISO tensile test piece of 4 mm thickness, preferably having a high bending strength measured based on ISO178. Specifically, the above-mentioned bending strength is preferably more than 200 MPa. In addition, the upper limit is as high as possible, but in fact, for example, less than 500 MPa.

[0123] The resin composition of the present embodiment is molded into an ISO tensile test piece of 4 mm thickness, preferably having a high flexural modulus measured based on ISO178. Specifically, the flexural modulus is preferably more than 9000 MPa. In addition, the upper limit is as high as possible, but in fact, for example, less than 20000 MPa.

[0124] <Method for producing resin composition>

[0125] The manufacturing method of the resin composition of the present embodiment is not particularly limited, and it is preferably a method using a single screw or twin screw extruder with a device that can be degassed from an exhaust port as a mixing machine. The above-mentioned crystalline thermoplastic resin component, a glass sheet with a thickness of 0.1 to 2 μm, a light-transmitting pigment, and other additives prepared as needed can be supplied to the mixing machine together, and other ingredients can also be supplied to the crystalline thermoplastic resin in sequence. In order to suppress crushing during mixing, inorganic fillers such as glass sheets with a thickness of 0.1 to 2 μm are preferably supplied from the middle of the extruder. In addition, two or more components selected from each component can also be pre-mixed and mixed.

[0126] In this embodiment, the light-transmitting pigment may be prepared by preparing a masterbatch of a thermoplastic resin such as polyamide 6 or polyamide 66, and then kneading the masterbatch with other components (thermoplastic resin, etc.) to prepare the resin composition in this embodiment.

[0127] <Production method of molded products>

[0128] The manufacturing method of the molded article using the resin combination of the present embodiment is not particularly limited, and the molding methods commonly used for thermoplastic resins, i.e., injection molding, hollow molding, extrusion molding, compression molding and other molding methods can be applied. The resin combination of the present embodiment is particularly suitable for the method of molding using a mold. In addition, it is suitable for the molding method of cooling by a mold.

[0129] The composition combination of this embodiment comprises the resin composition of this embodiment and a light-absorbing resin composition containing a thermoplastic resin and a light-absorbing pigment. The composition combination of this embodiment is preferably used for the production of a molded product by laser welding.

[0130] That is, the resin composition included in the composition combination functions as a light-transmitting resin composition, and the molded product formed by molding the light-transmitting resin composition becomes a resin member that transmits laser light during laser welding. On the other hand, the molded product formed by molding the light-absorbing resin composition becomes a resin member that absorbs laser light during laser welding.

[0131] <<Light-absorbing resin composition>>

[0132] The light-absorbing resin composition used in the present embodiment contains a thermoplastic resin (preferably a crystalline thermoplastic resin) and a light-absorbing dye.

[0133] Thermoplastic resins include polyamide resins, olefin resins, vinyl resins, styrene resins, acrylic resins, polyphenylene ether resins, polyester resins, polycarbonate resins, polyacetal resins, etc., and polyamide resins, polyacetal resins, polyester resins (preferably polybutylene terephthalate resins) are particularly preferred from the perspective of good compatibility with the resin composition, and polyamide resins are further preferred. In addition, the thermoplastic resin may be one or more than two.

[0134] The polyamide resin used in the light-absorbing resin composition is not limited in type, but the above-mentioned xylylenediamine-based polyamide resin is preferred.

[0135] The light-absorbing resin composition may further contain an inorganic filler, which may be a filler capable of absorbing laser light, such as glass flakes (particularly glass flakes with a thickness of 0.1 to 2 μm), glass fibers, carbon fibers, and inorganic powders coated with a laser-absorbing material.

[0136] Light-absorbing pigments refer to pigments that are not easily transmitted by laser light during laser cladding, compared with light-transmitting pigments. As light-absorbing pigments, light-absorbing pigments having a maximum absorption wavelength in the range of the irradiated laser wavelength, for example, in the range of wavelengths of 800nm ​​to 1100nm, can be exemplified. As an embodiment of the light-absorbing pigment in the present embodiment, the following pigments can be cited: 0.07 parts by mass of pigments are added to 100 parts by mass of polyamide resin (MP10 synthesized in the examples described later), melt-kneaded at a set temperature of 280°C of the extruder, and the obtained pellets are used, and the light transmittance at a wavelength of 1060mm measured by the method described in the examples described later is less than 2%. The mold temperature at this time is 110°C.

[0137] Specific examples of light-absorbing pigments include inorganic pigments (black pigments such as carbon black (e.g., acetylene black, lamp black, thermal black, furnace black, channel black, Ketjen black, etc.), red pigments such as iron oxide red, orange pigments such as molybdenum orange, white pigments such as titanium oxide), organic pigments (yellow pigments, orange pigments, red pigments, blue pigments, green pigments, etc.), etc. Among them, inorganic pigments are generally preferred because of their strong hiding power, more preferably black pigments, and even more preferably carbon black.

[0138] These light absorbing dyes may be used in combination of two or more. The content of the light absorbing dye is preferably 0.01 to 30 parts by mass based on 100 parts by mass of the thermoplastic resin.

[0139] In the composition combination of the embodiment, regarding the components other than the optical pigment in the transmissive resin composition for laser cladding, and the components other than the light-absorbing pigment in the light-absorbing resin composition, preferably more than 80 mass % are common, more preferably more than 90 mass % are common, and further preferably 95 to 100 mass % are common.

[0140] <<Laser cladding method>>

[0141] Next, the laser welding method is described. In this embodiment, a molded product (transmissive resin member) formed of the transmissive resin composition for laser welding of this embodiment and a molded product (absorbent resin member) formed of the above-mentioned light-absorbing resin composition can be laser welded to produce a molded product. By performing laser welding, the transmissive resin member and the absorbent resin member can be firmly welded without using an adhesive.

[0142] The shape of the component is not particularly limited. Since the components are joined to each other by laser cladding, they are usually in a shape with at least a surface contact portion (plane, curved surface). In laser cladding, the laser that passes through the transmissive resin component is absorbed by the absorbing resin component and melts, and the two components are clad. Here, the thickness of the component that transmits the laser (the thickness of the part that transmits the laser along the direction of laser transmission) can be appropriately determined considering the purpose, the composition of the resin composition and other factors, for example, less than 5 mm, preferably less than 4 mm. The lower limit of the thickness of the component that transmits the laser is, for example, more than 0.01 mm.

[0143] The laser light source used in laser welding can be determined according to the absorption wavelength of the light of the light absorbing pigment, and preferably a laser having a wavelength in the range of 800 to 1100 nm, for example, a semiconductor laser or a fiber laser can be used.

[0144] More specifically, for example, when welding a transmissive resin member and an absorbent resin member, first, the parts to be welded are brought into contact with each other. At this time, the welded parts of the two are preferably in surface contact, which may be a plane to a plane, a curved surface to a curved surface, or a combination of a plane and a curved surface. Next, a laser is irradiated from the transmissive resin member side. At this time, the laser can be focused on the interface between the two using a lens as needed. The focused beam is transmitted to the transmissive resin member, absorbed near the surface of the absorbent resin member, generates heat, and melts. Next, the heat is also transferred to the transmissive resin member through heat transfer, forming a molten pool at the interface between the two, and after cooling, the two are joined.

[0145] The molded product (laser welded product) formed by welding the transmissive resin member and the absorbent resin member as described above has high welding strength. It should be noted that the molded product of this embodiment includes not only finished products and parts, but also members that form a part of them.

[0146] The mechanical strength of the molded product obtained by laser cladding in the present embodiment is good, with high cladding strength, and the resin damage caused by laser irradiation is also less, so it can be applied to various uses such as various storage containers, electrical / electronic equipment parts, office automation (OA) equipment parts, household appliance parts, mechanical device parts, vehicle device parts, etc. In particular, it can be preferably used for food containers, pharmaceutical containers, oil and fat product containers, hollow parts for vehicles (various containers, intake manifold parts, camera housings, etc.), electrical parts for vehicles (various control units, ignition coil parts, etc.) motor parts, various sensor parts, connector parts, switch parts, circuit breaker parts, relay parts, coil parts, transformer parts, lamp parts, etc. The resin composition and composition combination of the present invention are particularly suitable for vehicle-mounted camera modules. In particular, the resin composition and composition combination of the present embodiment are suitable for vehicle-mounted camera housings and other hollow parts.

[0147] Example

[0148] Below, enumerate embodiment and the present invention is described more specifically.As long as do not depart from the gist of the present invention, the material, dosage, ratio, processing content, processing steps etc. shown in the following embodiment can be appropriately changed.Therefore, the scope of the present invention is not limited to the specific examples shown below.

[0149] When the measuring equipment used in the examples is difficult to obtain due to discontinuation of production, other equipment with equivalent performance may be used for measurement.

[0150] raw material

[0151] MP10: A polyamide resin composed of meta-xylylenediamine, para-xylylenediamine (MP molar ratio: 7:3) and sebacic acid, synthesized according to the description in paragraph 0071 of Japanese Patent Application Publication No. 2018-119043. The heat of crystallization measured by the following method is -0.5 mJ / mg.

[0152] MP6: A polyamide resin composed of m-xylylenediamine, p-xylylenediamine (molar ratio: 7:3) and adipic acid, synthesized according to the description of JP-A-2018-119043, paragraph 0072. The heat of crystallization measured by the following method is -0.5 mJ / mg.

[0153] PA66: polyamide 66, manufacturer: INVISTA Nylon Polymer Company, INVISTA U4800, heat of crystallization measured by the following method: -0.9 mJ / mg.

[0154] The heat of crystallization was measured using a differential scanning calorimeter as described below.

[0155] <Crystallization Heat>

[0156] The synthesized resin was pelletized and molded at a cylinder temperature of 280°C. The heat of crystallization of the obtained test piece (60×60×1 mm thick) was measured using differential scanning calorimetry (DSC) under the conditions of a heating rate of 10°C / min and 30 to 300°C.

[0157] The barrel temperature was set to 260°C when MP10 was used as the polyamide resin, 280°C when MP6 was used, and 280°C when PA66 was used. The mold surface temperature was set to 110°C when MP10 was used as the polyamide resin, 130°C when MP6 was used, and 90°C when PA66 was used.

[0158] As DSC, DSC7020 manufactured by Hitachi High-Tech Corporation was used.

[0159] The unit of heat of crystallization is mJ / mg.

[0160] Talc: Made by Hayashi Chemicals Co., Ltd., #5000S

[0161] Cuprous iodide: Copper(I)iodide manufactured by Nippon Chemical Industry Co., Ltd.

[0162] Potassium iodide: Made by Fuji Film Wako Pure Chemical Industries

[0163] Zinc stearate (II): manufactured by Fuji Film Wako Pure Chemical Industries

[0164] Release agent: Nitto Kasei Kogyo Co., Ltd., CS8CP, calcium montanate

[0165] Light-transmitting pigment: BASF Color & Effect Japan Co., Ltd., Lumogen (registered trademark) Black K0088 (formerly known as Lumogen Black FK 4281), pigment having a perylene skeleton

[0166] Inorganic filling materials

[0167] Glass fiber: ECS03T-211H manufactured by Nippon Electric Glass Co., Ltd.

[0168] Glass flake (fine flake): Microglass Fine Flake MEG160FY-M06 manufactured by Nippon Sheet Glass Co., Ltd., average thickness about 0.7 μm, aspect ratio 3 to 20

[0169] Examples 1 to 6, Comparative Examples 1 to 6

[0170] The pellets (resin composition) for forming a light-transmitting member described in the following Table 1 or 2 described later were produced.

[0171] Specifically, each component except the inorganic filler (glass fiber and glass flake) shown in the following Table 1 or 2 was weighed according to the ratio shown in Table 1 or 2 (unit is mass parts), and after dry mixing, it was fed from the screw root of a twin-screw extruder (made by Toshiba Machine Co., Ltd., TEM26SS) using a twin-screw box-type weigh feeder (made by KUBOTA, CE-W-1-MP). In addition, the inorganic filler was fed into the above-mentioned twin-screw extruder from the side of the extruder using a vibrating box-type weigh feeder (made by KUBOTA, CE-V-1B-MP), and melt-kneaded with the resin component, etc., to obtain pellets (resin composition) for forming a light-transmitting member.

[0172] The pellets for forming a light-transmitting member obtained above were dried at 120° C. for 4 hours, and then a test piece for a light-transmitting member (60 mm×60 mm×1.0 mm thick) was prepared using an injection molding machine (NEX140III-12EG manufactured by Nissei Plastic Industry Co., Ltd.).

[0173] The pellets obtained by the above-mentioned production method were dried at 120° C. for 4 hours and then injection-molded into ISO tensile test pieces (4 mm thick) using an injection molding machine (NEX140III-12EG manufactured by Nissei Plastic Industries, Ltd.).

[0174] During molding, the barrel temperature was set to 260°C when MP10 was used as the polyamide resin, 280°C when MP6 was used, and 280°C when PA66 was used. The mold temperature was set to 130°C (MP6), 110°C (MP10), and 90°C (PA66) depending on the type of polyamide resin as the main component of the resin component.

[0175] <Flexural strength and flexural modulus>

[0176] Based on ISO178, the flexural strength (unit: MPa) and the flexural modulus (unit: MPa) were measured at a temperature of 23°C using the above-mentioned ISO tensile test piece (4 mm thick).

[0177] <Warp evaluation>

[0178] The light-transmitting member test piece obtained above (60 mm × 60 mm × 1.0 mm thick) was placed on a reference table, and the height of the highest part (Max height, unit: mm) and the height of the lowest part (Min height, unit: mm) of the test piece were measured using a three-dimensional shape measuring instrument, and the difference was calculated. Specifically, Figure 1 As shown, the height of the reference table 1 is set to 0 mm, a light-transmitting member test piece 2 is placed, and the difference between the highest portion 3 and the lowest portion (usually the end of the test piece) at this height is measured as the warpage 4.

[0179] The three-dimensional shape measuring instrument used was VR-3200 manufactured by Keyence Corporation.

[0180] <Light transmittance>

[0181] The light transmittance at a wavelength of 1060 nm was measured for a test piece (60 mm×60 mm×1.0 mm thick) of the light-transmitting member obtained above, and the unit was expressed in %.

[0182] The light transmittance was measured using LMT-F1LC-PA manufactured by Tsubosaka Electric Co., Ltd.

[0183]

[0184]

[0185] It is clear from the above results that the light transmittance of the molded article formed by the resin composition of the present invention is high (Examples 1 to 6). In contrast, in Examples 1 to 6, when the same amount of glass fiber is added, the light transmittance is low (Comparative Examples 1 to 6). According to these results, it can be seen that when a glass sheet with a thickness of 0.1 to 2 μm is used instead of glass fiber as an inorganic filler, the light transmittance is improved.

[0186] Furthermore, the molded article formed from the resin composition of the present invention can maintain various mechanical strengths at high levels and can effectively suppress warping.

[0187] The resin composition described in Example 1 was not mixed with a light-transmitting pigment, but 3 parts by mass of a carbon black masterbatch (Carbon Black #45 manufactured by Mitsubishi Chemical Corporation) was mixed as a light-absorbing pigment, and the other steps were performed in the same manner to obtain pellets for forming an absorbent resin member. Using the pellets for forming a light-transmitting member obtained in Example 1 and the above-mentioned pellets for forming an absorbent resin member, according to paragraphs 0072, 0073 and Figure 1 It was confirmed that laser welding was performed appropriately.

Claims

1. A translucent resin composition for laser cladding, comprising 10 to 120 parts by mass of a glass sheet having a thickness of 0.1 to 2 μm and a translucent pigment, relative to 100 parts by mass of a crystalline thermoplastic resin, The numerical average of the aspect ratio of the glass sheet is 3 to 20, The crystalline thermoplastic resin comprises a polyamide resin, The polyamide resin is a semi-aromatic polyamide resin, The polyamide resin comprises a polyamide resin composed of a diamine-derived structural unit and a dicarboxylic acid-derived structural unit, wherein 70 mol% or more of the diamine-derived structural unit is derived from xylylenediamine, 70 mol% or more of the dicarboxylic acid-derived structural unit is derived from α,ω-straight-chain aliphatic dicarboxylic acid having 4 to 20 carbon atoms, the xylylenediamine is p-xylylenediamine and m-xylylenediamine, and 30 mol% or more of the xylylenediamine-derived structural unit is a m-xylylenediamine-derived structural unit. The α,ω-straight-chain aliphatic dicarboxylic acid having 4 to 20 carbon atoms is selected from pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, and dodecanedioic acid.

2. The resin composition according to claim 1, wherein The thickness of the glass sheet is 0.1 to 0.8 μm.

3. The resin composition according to claim 1, wherein The light-transmitting pigment has a perylene skeleton.

4. The resin composition according to claim 2, wherein The light-transmitting pigment has a perylene skeleton.

5. The resin composition according to any one of claims 1 to 4, wherein When the resin composition is molded into a molded article having a thickness of 60 mm×60 mm×1 mm, the warpage of the molded article is less than 1 mm. The warpage amount refers to the difference between the height of the highest part of the molded product placed on a reference stand and the height of the lowest part of the test piece.

6. The resin composition according to any one of claims 1 to 4, wherein The crystalline thermoplastic resin includes a polyamide resin having a crystallization heat of 0 to -1 mJ / mg when measured by a differential scanning calorimeter.

7. The resin composition according to claim 5, wherein The crystalline thermoplastic resin includes a polyamide resin having a crystallization heat of 0 to -1 mJ / mg when measured by a differential scanning calorimeter.

8. A composition comprising: The resin composition according to any one of claims 1 to 7, and A light-absorbing resin composition comprising a thermoplastic resin and a light-absorbing pigment. 9 . A molded article, which is formed by combining the resin composition according to claim 1 with the composition according to claim 8 .

10. A method for manufacturing a molded product, the method comprising: Laser welding is performed on a molded article formed of the resin composition according to any one of claims 1 to 7 and a molded article formed of a light-absorbing resin composition containing a thermoplastic resin and a light-absorbing dye.

Citation Information

Patent Citations

  • Heat accumulating tank system of temperature laminar type

    JP1988220027A

  • Polyamide resin composition for laser welding, molded article and manufacturing method of molded article

    JP2008308526A

  • Polyamide resin composition and conductive shaft-like molding

    JP2011132550A

  • Partially aromatic and partially crystalline copolyamide

    JP2013513681A

  • Polyamide resin composition and molded article

    JP2018095706A